The analysis of wood harvesting restrictions in conservation areas and old-growth forests of the Republic of Karelia - Gerasimov, Yuri; Markovsky, Alexander; Markovskaya, Natalia; Lapshin, Petr (Finnish Forest Research Institute, 2006)
An analysis of the current state and wood harvesting restrictions in officially existing and planned conservation areas as well as unofficial old-growth forests of the Republic of Karelia is provided in this paper. Old-growth forests are suggested by NGOs and these forests do not have wood harvesting restrictions according to Russian legislation. However, environmentally responsible forest industries companies do not procure wood from these forests.In the beginning of 2006 Karelia has 215 official conservation areas with the total area of 933.2 thousand ha (6.3% of the total forest fund of Karelia). All types of fellings are prohibited in 58 official conservation areas (448.1 thousand ha or 3% of the forest fund of Karelia). Final fellings (or clearcut) are prohibited in 23 official conservation areas (151.1 thousand ha or 1% of the forest fund of Karelia). The rest of the conservation areas (345 thousand ha or 2.3% of the forest fund of Karelia) have no restrictions for wood harvesting. Three officially planned conservation areas (105.6 thousand ha or 0.7% of the forest fund of Karelia) have been clearly recognized; the Kalevalsky national park (74 thousand ha) has restrictions for wood harvesting. NGOs have suggested 40 detached areas of old-growth forests (approximately 980 thousand ha or 6.6% of the forest fund of Karelia). The major areas of old-growth forests are located in Kemsky, Muezersky, Kostomukshsky, Pudozhsky, Pialmsky Piaozersky, Sosnovetsky, Chupinsky and Yushkozersky leskhozes. Locations of conservation areas and old-growth forests are shown in the whole Karelia, at forest district ( leskhoz ) and at forest block ( kvartal ) levels.
Анализ ограничений лесопользования на особо охраняемых природных территориях и в малонарушенных лесах Республики Карелия - The analysis of wood harvesting restrictions in conservation areas and old-growth forests of the Republic of Karelia
Keywords: Venäjän Karjala; puunhankinta; suojelualueet; vanhat metsät; conservation areas; Karelia; old-growth forests; Russia; wood procurement